DOES AUDIT FIRMS REPUTATION MATTER? FIRM AND AUDIT CHARACTERISTICS IN AUDITOR SWITCHING ON INDONESIAN ENERGY COMPANIES - Rahayu, Ruci Arizanda; Haryanto, Sendy Dwi; Alfarizi, Luthfi (International Journal Multidisciplinary (IJMI), 2025)
Objective: This study aims to investigate the role of audit firms' reputation as a moderating variable in the relationship between company characteristics and audit characteristics affecting auditor switching decisions. The focus is on energy companies listed on the Indonesia Stock Exchange. Method: The research utilizes panel data from 55 energy companies, selected through purposive sampling from a population of 79 companies, covering the period 2018–2021. Logistic regression and moderated regression analysis were performed using SPSS 26 to analyze the data.  Results: The findings reveal that audit opinion, audit delay, and financial distress have a significant influence on auditor switching. Additionally, the reputation of audit firms moderates the relationship between financial distress and auditor switching, emphasizing its critical role in shaping such decisions. Novelty: This study contributes to the literature by providing empirical evidence on the moderating effect of audit firms' reputation in the context of Indonesia's energy sector. It offers valuable insights for stakeholders in emerging markets to understand auditor switching dynamics and make informed decisions in the audit environment.